BS EN IEC 61169-10. Radio-frequency connectors. Part 10. R.F. coaxial connectors with inner diameter of outer conductor 3 mm (0.12 in) with snap-on coupling. Characteristic impedance 50 ohms (Type SMB) (17th December 2021) - British Standards Institution,
No abstract available